An acoustic system for EOL engines diagnoses in hot test cells. (July 2020) - Masullo, M; Maffei, L; Bianco, B; Ambrosio, V; Ricciardi, S
Abstract: End of Line tests have a crucial role in industrial processes to validate the products' quality. In automotive industry, engines at the end of assembling process are fully tested within hot test cells at different working conditions by mean specific test cycles. Vibration monitoring is widely used in order to identify potential faults in the assembly process. This contact technique leads to several disadvantages, mainly due to the accessibility and the characteristics of surfaces for accelerometers mounting (e.g. rotating parts, geometries complexes, high temperatures) and to the time-consuming setup procedures. These limitations can be overcome by using microphone sensors. This paper describes the development phases of an acoustic based fault diagnosis system, its integration on hot test cells and the results obtained over large number of engines tested. By mean some specific technical solutions the acoustics approach in the EOL fault diagnosis of combustion engines has showed itself to be compatible with the characteristics of the production industry environment, providing reliable and repeatable results. The latter has been demonstrated also by comparison with the traditional accelerometer technique.